2008
DOI: 10.2136/sssaj2007.0279
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification and Nitrate Consumption in an Herbaceous Riparian Area and Perennial Ryegrass Seed Cropping System

Abstract: Davis et al. (2006) found that <1.2% of applied 15 NO 3 − ended up in the microbial biomass of an herbaceous riparian zone, 2 mo after application. Yin et al. (2002), however,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 70 publications
2
20
0
1
Order By: Relevance
“…These results are consistent with higher DEA in riparian buffers compared with crop fields (Groffman et al, 1993;Kim, 2008). Consistent with previous work (Davis et al, 2008), we also observed a positive correlation between TOC and DEA as well as NH 4 + -N and DEA. The positive relationship between NH 4 + -N and DEA could be due to (i) NH 4 + -N regulation of NO 3 − -N consumption and production (Davis et al, 2008) or (ii) it can be an indirect relationship resulting positive correlations among TOC, NH 4 + -N, potentially mineralizable C, and N mineralization (Schomberg et al, 2009;Haddad et al, 2013).…”
Section: In Situ Nitrous Oxide Fluxessupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with higher DEA in riparian buffers compared with crop fields (Groffman et al, 1993;Kim, 2008). Consistent with previous work (Davis et al, 2008), we also observed a positive correlation between TOC and DEA as well as NH 4 + -N and DEA. The positive relationship between NH 4 + -N and DEA could be due to (i) NH 4 + -N regulation of NO 3 − -N consumption and production (Davis et al, 2008) or (ii) it can be an indirect relationship resulting positive correlations among TOC, NH 4 + -N, potentially mineralizable C, and N mineralization (Schomberg et al, 2009;Haddad et al, 2013).…”
Section: In Situ Nitrous Oxide Fluxessupporting
confidence: 93%
“…Consistent with previous work (Davis et al, 2008), we also observed a positive correlation between TOC and DEA as well as NH 4 + -N and DEA. The positive relationship between NH 4 + -N and DEA could be due to (i) NH 4 + -N regulation of NO 3 − -N consumption and production (Davis et al, 2008) or (ii) it can be an indirect relationship resulting positive correlations among TOC, NH 4 + -N, potentially mineralizable C, and N mineralization (Schomberg et al, 2009;Haddad et al, 2013). Opposite patterns of in situ N 2 O fluxes and DEA across the watershed treatments led us to pursue denitrification measurements.…”
Section: In Situ Nitrous Oxide Fluxessupporting
confidence: 93%
“…Under anaerobic conditions, sulphide stimulates DNRA, by serving as an electron donor, and depresses denitrification, by repressing NO and N 2 O reductase (Myers, 1972;Brunet and Garcia-Gill, 1996). In this line DeCatanzaro et al (1987) found in the above mentioned study a stimulation of DNRA when simultaneously adding glucose and sulphide, which contrasted the finding from only glucose addition.…”
Section: Environmental Conditions For Dnramentioning
confidence: 57%
“…Chen et al (1995) identified several possible explanations, including the high native soil C content compared to the amount of added glucose, unfavourable redox conditions for DNRA or effects of soil rewetting. DeCatanzaro et al (1987) also did not find an effect of glucose addition on DNRA, but revealed that DNRA was stimulated by alfalfa addition. This was apparently an effect of sulphur in alfalfa, which was released as -SH group during sulphur mineralisation of organic matter and served as reducing agent.…”
Section: Environmental Conditions For Dnramentioning
confidence: 85%
See 1 more Smart Citation